APPRAISAL OF CHARACTERS IN GEUNYEO-E IREUMEUN AND INDONESIAN TRANSLATION HER NAME IS - Binar Candra Auni; Haru Deliana Dewi (STBA LIA - Jakarta, 2022)
ABSTRACT This study is a descriptive qualitative study that discusses the appraisal of characters found in the Korean anthology, 그녀의 이름은 (Geunyeo-e ireumeun) and its Indonesian translation, Her Name Is. This study focuses on the characters’ judgment in the Korean text (source text or ST), and the Indonesian text (target text or TT). It aims to describe the appraisal of the female lead character towards other characters, other characters towards the female lead character, and the female lead character towards herself. The data that were collected through the linguistic corpus method were then analyzed by comparing judgments found in the ST and TT. It is found that there are 97 pairs of the characters’ judgments. The result of the analysis shows that both in the ST and in the TT, the judgment of the female lead character towards her partner and society is dominantly negative (71.43%). Moreover, most of the judgment of the partner and society towards the female lead character is also negative (66.67%). Although the judgment of other female characters towards the female lead character tends to be negative (75%), there is no significant percentage gap between the positive judgments (53.33%) and negative judgments (46.67%) of the female lead character towards other female characters. Furthermore, it is found that the judgment of the lead female character towards herself is neutral. This study also discovered that the female lead character of each story is the main focalizer both in the ST and in the TT. ABSTRAK Penelitian ini membahas appraisal yang berfokus pada tokoh-tokoh dalam antologi cerpen Korea 그녀의 이름은 (Geunyeo-e ireumeun) dan terjemahan Indonesia, Her Name Is. Penelitian menganalisis attitude judgment para tokoh dalam teks sumber (TSu) bahasa Korea dan teks sasaran (TSa) bahasa Indonesia sebagai korpus paralel. Penelitian ini adalah penelitian kualitatif deskriptif dan menggunakan linguistik korpus untuk pengumpulan data. Data judgment kedua teks kemudian dibandingkan dengan bantuan anotasi korpus. Penelitian bertujuan untuk menggambarkan appraisal tokoh utama wanita terhadap tokoh lain, tokoh lain terhadap tokoh utama wanita, dan tokoh utama wanita terhadap dirinya sendiri. Hasil analisis menunjukkan bahwa dari total 97 pasang data, judgment tokoh utama wanita kepada pasangan dan masyarakat cenderung negatif (71,43%), dan begitu pula sebaliknya, judgment pasangan dan masyarakat terhadap tokoh utama wanita bersifat negatif (66,67%). Sementara itu meski judgment tokoh wanita lain terhadap tokoh utama wanita dominan negatif (75%), persentase judgment positif dan negatif tokoh utama wanita terhadap tokoh wanita lain tidak jauh berbeda (53,33%). Selanjutnya ditemukan bahwa judgment tokoh utama wanita terhadap dirinya sendiri netral. Judgment para tokoh dipengaruhi oleh pandangannya terhadap Konfusianisme di Korea Selatan. Selain itu, peneliti menemukan bahwa tokoh utama wanita adalah fokalisator utama dari antologi cerpen ini. Keywords: appraisal, attitude, cerpen Korea